the LAST piece of my HEART - Toon, Paige, 1975- (London, England : Simon & Schuster UK Ltd., 2017)
When life feels like a puzzle, sometimes it's the small pieces that make up the bigger picture...Join Bridget on a journey to put her world back together. A successful travel journalist, Bridget has ambitions to turn her quirky relationship blog about the missing pieces of her heart into a book. But after a spate of rejections from publishers, she accepts an alternative proposition. Nicole Dupre died leaving behind a bestselling novel and an incomplete sequel. Tasked with finishing the book, Bridget is thankful to have her foot in the publishing door, even if it means relocating to Cornwall for the summer and answering to Nicole's grieving husband, Charlie...
Keywords: English fiction; Man-woman relationships -- Fiction; Widowers -- Fiction